Chronic Intestinal Failure and Short Bowel Syndrome in Adults: The State of the Art - Vara-Luiz,Francisco (2024)
Abstract Background: Short bowel syndrome (SBS) is a devastating malabsorptive condition and the most common cause of chronic intestinal failure (CIF). During the intestinal rehabilitation process, patients may need parenteral support for months or years, parenteral nutrition (PN), or hydration/electrolyte supplementation, as a bridge for the desired enteral autonomy. Summary: Several classiﬁcation criteria have been highlighted to reﬂect different perspectives in CIF. The management of CIF-SBS in adults is a multidisciplinary process that aims to reduce gastrointestinal secretions, slow transit, correct/prevent malnutrition, dehydration, and speciﬁcnutrient deﬁciencies, and prevent refeeding syndrome. The nutritional support team should have the expertise to take care of these complex patients: ﬂuid support; oral, enteral, and PN; disease/PN-related complications; pharmacologic treatment; and surgical prevention/treatment. Key Messages: CIF-SBS is a complex disease with undesired consequences, if not adequately identiﬁed and managed. A comprehensive approach performed by a multi-disciplinary team is essential to reduce PN dependence, promote enteral independence, and improve quality of life.